Analisis Faktor Yang Mempengaruhi Prestasi Kerja Guru Sekolah Dasar Pada Kelompok Kerja Kepala Sekolah (KKKS) Kecamatan Jeunieb Kabupaten Bireuen - Mutasirullah, Mutasirullah; Konadi, Win; Yanna, Sri (Singkite Journal, 2022)
This study aims to analyze the influence of the principal's leadership, organizational culture and work environment on the work performance of elementary school teachers in the Principal Working Group (KKKS) of Jeunieb District, Bireuen Regency. The results of the path analysis show, 1) There is a direct and indirect effect of the principal's leadership on teacher performance by 37.25%. 2) There is a direct and indirect effect of organizational culture on teacher performance of 34.15%. 3) There is a direct and indirect effect of the work environment on teacher performance by 42.9%. 4) Simultaneously the principal's leadership, organizational culture and work environment on the work performance of elementary school teachers studied were 54.2%.